EAMS webinar March 2021: Pragmatic guide to awake videolaryngoscope guided intubation. (October 2021) - Chiesa, P.; Sorbello, M.; Greif, R.; Hodzovic, I.
Abstract: Awake tracheal intubation remains the gold standard for managing a predicted difficult airway. There is emerging evidence that supports the use of videolaryngoscope guided awake intubation. Videolaryngoscopes have become widely available and consequently easy to use and familiar to anaesthetists, allowing for observed tube placement and fixed wide view of the glottis throughout the intubation procedure. This article summarizes the key points and provides answers to the main audience questions from the EAMS March 2021 Webinar. Topics discussed include optimal patient and operator positioning, techniques of applying topical anaesthesia to the airway, testing for adequacy of airway anaesthesia, videolaryngoscope blade insertion and tracheal tube placement and sedation for awake intubation.